Are nontariff measures and tariffs substitutes? Some panel data evidence - Niu, Zhaohui; Milner, Chris; Gunessee, Saileshsingh; Liu, Chang (Wiley-Liss Inc., 2020)
Using new estimates of ad valorem equivalent of nontariff measures (NTMs) over time, this paper examines NTMs and tariffs’ relationship for a sample of 70 economies for 4,949 products at the 6‐digit harmonized system level over the period 2003–2015. A panel data methodology models the lagged adjustment of NTMs to tariffs, consistent with a causal relationship. Trade policy substitution is found when the models are estimated in both levels and changes; with this holding for both OECD and non‐OECD countries, but not for the agriculture sector in OECD countries. Overall, there is a fairly complete substitution between policy instruments in absolute terms.